Rethinking diabetes in the United States - Herman, William H.; Schillinger, Dean (Frontiers in Endocrinology, 2023)
Despite the availability of effective medical treatments, the diabetes epidemic has accelerated in the United States and efforts to translate treatments into routine clinical practice have stalled. The National Clinical Care Commission (NCCC) was established by the Congress to make recommendations to better leverage federal policies and programs to more effectively prevent and treat diabetes and its complications. The NCCC developed a guiding framework that incorporated elements of the Socioecological and Chronic Care Models. It gathered information from both health-related and non-health-related federal agencies, held 12 public meetings, solicited public comments, met with numerous interested parties and key informants, and performed comprehensive literature reviews. The final report of the NCCC was transmitted to the Congress in January 2022. It called for a rethinking of the problem of diabetes in the United States, including the recognition that the lack of progress is due to a failure to confront diabetes as both a complex societal problem as well as a complex biomedical problem. To prevent and control diabetes, public policies and programs must be aligned to address both social and environmental determinants of health and health care delivery as they impact diabetes. In this article, we discuss the findings and recommendations of the NCCC as they relate to the social and environmental factors that influence the risk of type 2 diabetes and argue that the prevention and control of type 2 diabetes in the U.S. must begin with concrete population-level interventions to address social and environmental determinants of health.